Dynamics of Thermoacoustic Oscillations in Swirl Stabilized Combustor without and with Porous Inert Media. (21st February 2022) - Dowd, Cody; Meadows, Joseph
Abstract : Lean premixed (LPM) combustion processes are of increased interest to the gas turbine industry due to their reduction in harmful emissions. These processes are susceptible to thermoacoustic instabilities, which are produced when energy added by an in-phase relationship between unsteady heat release and acoustic pressure is greater than energy dissipated by loss mechanisms. To better study these instabilities, quantitative experimental resolution of heat release is necessary, but it presents a significant challenge. Most combustion systems are partially premixed and therefore will have spatially varying equivalence ratios, resulting in spatially variant heat release rates. For laminar premixed flames, optical diagnostics, such as OH chemiluminescence, are proportionally related to heat release. This is not true for turbulent and partially premixed flames, which are common in commercial combustors. Turbulent eddies effect the strain on flame sheets which alter light emission, such that there is no longer a proportional relationship. In this study, phased, averaged, and spatially varying heat release measurements are performed during a self-excited thermoacoustic instability without and with porous inert media (PIM). Previous studies have shown that PIM can passively mitigate thermoacoustic instabilities, and to the best of the authors' knowledge, this is the first-time that heat release rates have been quantified for investigating the mechanisms responsible for mitigating instabilities using PIM. Heat release is determined from high-speed PIV and Abel inverted chemiluminescence emission. OH ∗ chemiluminescence is used with a correction factor, computed from a chemical kinetics solver, to calculate heat release. The results and discussion show that along with significant acoustic damping, PIM eliminates the direct path in which heat release regions can be influenced by incoming perturbations, through disruption of the higher energy containing flow structures and improved mixing.